Datura species (Dhatura Safed and Dhatura Seyah): A Review with special emphasis on single-use and compound formulations and pharmacological studies relevant to Unani System of Medicine - Kalam, Mohd Afsahul; Rifat, Iqra (Indian Journal of Integrative Medicine, 2021)
Background: Datura is a genus belonging to family Solanaceae, consisting of 15 species that include annual and perennial herbs, shrubs, and trees. In the Unani System of Medicine, two varieties are commonly used for medicinal purposes. One is black called Dhatura Seyah which is obtained from Datura stramonium and D. niger, and second is Dhatura Safed (white) obtained mainly from two sources D. metel and D. innoxia. All the species are poisonous especially their seeds and flowers but used medicinally after detoxification by specific methods and along with their correctives mentioned in Unani Tibb. Methods: The literature search was performed using online databases including PubMed and Google Scholar and relevant information were extracted from articles. Results: Various scientific studies have been done and the drug is proved as an anti-catarrhal, anti-cancerous, anthelmintic, anti-rheumatic, anesthetic, and anti-diarrheal. Different species of datura used in Unani Medicine for the management of various ailments have been justified through various pharmacological researches like analgesic, sedative, antidiabetic, and anti-ulcer properties. These plants are important for pharmacological research and drug development, not only when bioactive phytocompounds are used directly as therapeutic agents, but also as starting materials for the synthesis of drugs or as models for pharmacologically active compounds. Conclusions: This review gives an account of the current knowledge on the morphology, phytochemistry, and pharmacological aspects of all the species of Datura along with its action and uses in the perspective of Unani Medicine.